The qualities of core kenaf particle boards were studied. The boards were made of core kenaf particles and their liquids fortified by melamine formaldehyde. Core kenaf liquids were prepared using 20 – 60 mesh particles, phenol : formaldehyde ratio of 0,5, based on Masri (2005). SNI 06-4567-1998 and JIS A 5908-2003 were used to grade the kenaf liquids and particle board. Factorial analysis 3 x 3 in Complete Randomized Design was applied with 2 replications. Glue spread with 3 levels (10, 15 a - Surdiding RUHENDI (Departemen Hasil Hutan, IPB, 2008)
The qualities of core kenaf particle boards were studied. The boards were made of core kenaf particles and their liquids fortified by melamine formaldehyde. Core kenaf liquids were prepared using 20 – 60 mesh particles, phenol : formaldehyde ratio of 0,5, based on Masri (2005). SNI 06-4567-1998 and JIS A 5908-2003 were used to grade the kenaf liquids and particle board. Factorial analysis 3 x 3 in Complete Randomized Design was applied with 2 replications. Glue spread with 3 levels (10, 15 and 20% of the oven dry weight kenaf particles) and fortification MF with 3 levels (15, 30 and 45% of the solid content of the kenaf liquids) were used. Kenaf particles were cold soaked prior bonding. The condition of bonding operation in making particle board were : pressure of 20 kgf/cm2 at 160ºC for 12 minutes. The best result of particle board produced by 20% glue spread and 45% MF fortification with the properties as follows : density of 0,7 g/cm3, moisture content of 6,6%, water absorb ability of 55,6%, thickness swelling of 16,6%, screw holding strength of 641,2 N, internal bond of 0,86 N/mm2, MOE of 2131,9 N/mm2, and MOR of 15,3 N/mm2. Fortifications doesn’t significantly affect the quality of the particle boards. Keywords: Core-kenaf, kenaf liquids, fortification.